Environmental zoning and coastal zone conservation: the case of a protected area in Northeastern Brazil - Rêgo,Ilanna de Souza (2016)
Conservation of coastal zones is a matter of debate all around the world. In this context, marine protected areas can be counted as legal instruments to ensure proper use of natural resources and promote sustainable development. One of the main aspects for the management of protected areas is environmental zoning. Despite its importance, there are few studies focusing on environmental zoning in semiarid coastal environments. The purpose of this study was to present a case study on environmental zoning of a protected area located in the Environmental Protection Area of the Curú River estuary, which is located on the semiarid coast of the South Atlantic Ocean in Ceará-Brazil. The research was conducted in accordance with the classification criteria used in the Ecological-Economic Zoning (EEZ) of the Coastal Zone, a legal instrument that is important with regards to the Brazilian coast. The work was performed with a GIS technique and involved field activities. The results suggest the following environmental systems within the perimeter of the protected area: river plain, fluvial-marine plain with mangroves, fixed dunes, plain deflation/mobile dunes, plain deflation/fixed dunes, pre-coastal vegetation, and sandspit. The maps of the environmental systems zoning were developed on a 1:40,000 scale and were made to encourage the sustainable use of natural resources. As pressure on the environment by human activities increases, it is essential to update environmental zoning in protected areas, especially in the coastal areas of developing countries.